The lucky lamb - Daniels, Lucy; Ellis, Andy (Hodder Children's London, 2002)
It's too cold outside for Woolly, the first new born lamb of the season. But when he's inside, Woolly gets into all sorts of trouble. Then Mandy has a brilliant idea to bring Woolly and his mum back together